Synthesis, Spectral Characterization and Antioxidative Evaluation of Substituted 4H-1,4-Benzothiazine and Their Sulfones - Gautam, Naveen; Sharma, Meenakshi; Gautam, Vibha; Sharma, M.K.; Gautam, D.C. (Asian Journal of Chemistry, 2010)
4H-1,4-Benzothiazines are synthesized by condensation followed by oxidative cyclization of 2- aminobenzenethiols with b-diketones in presence of dimethyl sulfoxide. The sulfones of these 4H-1,4-benzothiazines were synthesized by treating them with 30 % hydrogen peroxide in glacial acetic acid. Synthesized compounds found to be antioxidants on the basis of certain analysis. Spectral evaluation and confirmation are done by IR, 1H NMR and mass spectral data techniques.